Agostic Hydrogens in 1‐Norbornyl Metal Cyclopentadienyl Structures. Issue 44 (9th November 2020) - Fan, Zhixiang; Hu, Yuchen; Li, Huidong; Fu, Jia; Fan, Qunchao; King, R. Bruce; Schaefer, Henry F.
Abstract : The first‐row transition metal 1‐norbornyl derivatives CpM(nor) Cp = η 5 ‐C5 H5 ; nor = 1‐norbornyl; M = Ti to Cu), including the experimentally known CpNi(nor) reported by Lehmkuhl and Dimitrov, have been examined by density functional theory and benchmarked by the more accurate DLPNO‐CCSD(T) method. The lowest energy CpM(nor) structures for the later first row transition metals from manganese to copper are found to be high‐spin state structures in which the 1‐norbornyl ligand is bonded to the metal only through the M–C σ‐bond to the bridgehead carbon atom. The favored spin states range from doublet for CpCu(nor) to sextet for CpMn(nor). The pattern of favorable structure types changes for the CpM(nor) derivatives of the earlier first row transition metals to the left of manganese since all of their low energy structures have singly or doubly agostic 1‐norbornyl groups. The agostic C–H–M interactions in the CpM(nor) derivatives are characterized by their reduced density gradients and low ν(C–H) frequencies. Abstract : The lowest energy CpM(nor) structures from Mn to Cu are high‐spin state structures with no agostic hydrogen atoms from the 1‐norbornyl group. However, the lowest energy CpM(nor) structures for Cr back to Ti all have one or two agostic hydrogens from the 1‐norbornyl group.